Man is a Beast for the Animals - Pimentel Chacón, Jonathan (2022)
The article develops the idea according to which Max Jiménez´s El Jaul affirms that the most distinctive feature of the men and women that form the Costa Rican nation is a bestiality that is manifested particularly against animals. Consequently, Jimenez´s unusual bestiary disputes the peaceful and benevolent relationship that is imagined as a fundamental mark of the “most pure national lineage”.